2000
DOI: 10.1007/s005950050026
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies of Colorectal Cancers that Developed Following Pelvic Irradiation

Abstract: Radiation therapy is believed to be a predisposing factor in the development of carcinoma. During the period from 1974 to 1997, we treated five colorectal cancers in four patients who had undergone pelvic irradiation for cervical cancer. Radiation-induced changes in the remaining bowel were recognized in all of these patients. Of the five tumors, two were histologically diagnosed as mucinous adenocarcinoma, demonstrating a higher distribution than usual: To clarify the characteristics of the tumors, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several authors have reported an association between the presence of a specific codon 12 K-ras gene mutation and the mucinous histotype in colorectal carcinomas (Nakao et al, 2000;Bazan et al, 2002) and in intestinal-type ovarian carcinomas (Gemignani et al, 2003). Several authors have reported an association between the presence of a specific codon 12 K-ras gene mutation and the mucinous histotype in colorectal carcinomas (Nakao et al, 2000;Bazan et al, 2002) and in intestinal-type ovarian carcinomas (Gemignani et al, 2003).…”
Section: Kras Mutation Incidencementioning
confidence: 99%
“…Several authors have reported an association between the presence of a specific codon 12 K-ras gene mutation and the mucinous histotype in colorectal carcinomas (Nakao et al, 2000;Bazan et al, 2002) and in intestinal-type ovarian carcinomas (Gemignani et al, 2003). Several authors have reported an association between the presence of a specific codon 12 K-ras gene mutation and the mucinous histotype in colorectal carcinomas (Nakao et al, 2000;Bazan et al, 2002) and in intestinal-type ovarian carcinomas (Gemignani et al, 2003).…”
Section: Kras Mutation Incidencementioning
confidence: 99%